2004
DOI: 10.4161/cbt.3.7.920
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tumor co-transfection with superantigen and CD80 induces systemic immunity without tolerance and prolongs survival in mice with hepatocellular carcinoma

Abstract: Background. Since transfection of established tumors with immunostimulatory genes can elicit antitumor immunity, we treat mouse HCC with in vivo transfection of superantigen SEA and/or costimulatory molecule CD80 and evaluated the safety and efficacy.Methods. Mice with HCC were treated with lipid-complexed plasmid DNA encoding staphylococcal enterotoxin A and/or CD80. Then the mice were evaluated for tumor regression, systemic immunologic responses, survival times and treatment-associated toxicity.Results. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Accumulating data have revealed that costimulatory molecules are often downregulated or lost in HCC cells (Fujiwara et al 2004;Tatsumi et al 1997). Previous investigators have shown that the genetic modiWcation of HCC cells to express elevated levels of costimulatory molecules can elicit protective and sometimes curative immunity against unmodiWed HCC tumor cells (Li et al 2004). In addition, the expression of many costimulatory molecules in a tumor cell seems to be more eYcient than the expression of single molecule in eliciting tumor-speciWc T-cell immunity (Disis et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Accumulating data have revealed that costimulatory molecules are often downregulated or lost in HCC cells (Fujiwara et al 2004;Tatsumi et al 1997). Previous investigators have shown that the genetic modiWcation of HCC cells to express elevated levels of costimulatory molecules can elicit protective and sometimes curative immunity against unmodiWed HCC tumor cells (Li et al 2004). In addition, the expression of many costimulatory molecules in a tumor cell seems to be more eYcient than the expression of single molecule in eliciting tumor-speciWc T-cell immunity (Disis et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…8,9 Our lab has made an effort to establish effective immunotherapy in recent few years. [10][11][12] In view of the fact that HLA-A2 is positive in 53.5% of HCC patients in China population, 13 it is valuable to investigate whether the epitope of MAGE-n antigen presented by HLA-A2 could induce primary, peptide-specific CTL against HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Another strategy consists in direct transfection of a SAg into the tumor, which elicits local and systemic immune responses and leads to tumor regression without systemic toxicity. [22][23][24] The present study was designed to test the ability of a synthetic cationic polymer, polyethylenimine (PEI), to deliver a SAg, namely the SEA, to tumor cells in vivo and to induce an antitumor immune response and tumor regression. For that purpose, a transmembrane SEA fusion construct (pSEA-TM) was complexed with PEI and injected, in the presence of epinephrine to improve in vivo transfection efficiency, into tumors induced by subcutaneous injection of a melanoma cell line into syngeneic mice.…”
Section: Introductionmentioning
confidence: 99%